2021
DOI: 10.1080/02255189.2020.1862071
|View full text |Cite
|
Sign up to set email alerts
|

Global citizenship amid COVID-19: why climate change and a pandemic spell the end of international experiential learning

Abstract: même si tout cela devra avoir lieu chez soi, et en ligne. Le réchauffement climatique et la pandémie de COVID-19 sont des problèmes globaux. Il faudra pour leur faire face que l'éducation en citoyenneté mondiale aille beaucoup plus loin que le simple apprentissage expérientiel par le biais de l'apprentissage par le service. Au contraire, il lui faudra reconnaitre que l'on peut trouver un sens aux défis mondiaux actuels, y compris par le biais de l'activisme de l'anthropocène.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Additionally, the combination of both frustration and learning was illustrated in the statement, “USP helped me reconcile with the fact that many of my academic peers come from privileged backgrounds, so they don't have the fundamental mentality to acknowledge life on the other side of the spectrum… I felt the weight of my racial identity the entire duration of my USP learning experience.” Findings supported recommendations from Lee and Green (2016) of the need for race conscious academic intentionality in study abroad due to the “complex relationships between education abroad participants’ identities and their experiences, learning, and challenges in host communities” (p. 64). Black racial identity development and Latinx identity development were evidenced in critical student reflections self-identified as resulting from “first-time” lived experiences in the racial majority in the East African context.…”
Section: Findings and Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Additionally, the combination of both frustration and learning was illustrated in the statement, “USP helped me reconcile with the fact that many of my academic peers come from privileged backgrounds, so they don't have the fundamental mentality to acknowledge life on the other side of the spectrum… I felt the weight of my racial identity the entire duration of my USP learning experience.” Findings supported recommendations from Lee and Green (2016) of the need for race conscious academic intentionality in study abroad due to the “complex relationships between education abroad participants’ identities and their experiences, learning, and challenges in host communities” (p. 64). Black racial identity development and Latinx identity development were evidenced in critical student reflections self-identified as resulting from “first-time” lived experiences in the racial majority in the East African context.…”
Section: Findings and Discussionsupporting
confidence: 56%
“…Findings support the contentions of Duncan et al (2020) of the importance of safe learning environments to achieve desired student learning outcomes with new insights of the importance of inclusion of racial bias learning as part of the necessary “safe learning environments” for American BIPOC students studying abroad. Supporting Lee and Green (2016), this case study reinforces the need for race-conscious academic intentionality in study abroad because of the “complex relationships between education abroad participants’ identities and their experiences, learning, and challenges in host communities” (p. 42). This case study provides new support to an urgent call to action for implementation of intentional anti-racism program designs in study abroad programs in order to support the emotional, social, and academic frustrations and particular dangers that U.S. BIPOC students disproportionately encounter in the East African context and potentially in other study abroad contexts.…”
Section: Findings and Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…With the advances of information and communication technology (ICT), some teachers have opted for gamification, virtual reality, augmented reality and software like Google Earth to provide simulation and inclusive experience of historical events (Konstantinov et al, 2018;Castro-Calviño et al, 2020). Through first-person experience and experiential learning, students are able to boost their motivation and improve their understanding of inequality, social justice and the causes of poverty, provoking reflection on relevant local and global issues (Adetunji et al, 2018;Konstantinov et al, 2018;Huish, 2021). The effectiveness of teaching has been boosted due to an increase in knowledge, cultural awareness and motivation of learners.…”
Section: The Relationship Between Cultural Heritage Buildings and Lea...mentioning
confidence: 99%
“…The effectiveness of teaching has been boosted due to an increase in knowledge, cultural awareness and motivation of learners. Notably, with the impact of the COVID-19 pandemic, Huish (2021) suggested that virtual learning spaces can overcome the restrictions of the traditional classroom in adopting new policies and promoting Students' activism and promotion of global citizenship. Therefore, it can be seen from the current literature that incorporating digitized cultural heritage buildings has the potential to achieve the benefits of SDG 4 (quality education) in terms of raising awareness of cultural diversity and global citizenship.…”
Section: The Relationship Between Cultural Heritage Buildings and Lea...mentioning
confidence: 99%